Copy Number Variations Due to Large Genomic Deletion in X-Linked Chronic Granulomatous Disease - Arai, Takashi; Oh-ishi, Tsutomu; Yamamoto, Hideaki; Nunoi, Hiroyuki; Kamizono, Junji; Uehara, Masahiko; Kubota, Takeo; Sakurai, Takuya; Kizaki, Takako; Ohno, Hideki (PloS one, 2012)
Mutations in genes for any of the six subunits of NADPH oxidase cause chronic granulomatous disease (CGD), but almost 2/3 of CGD cases are caused by mutations in the X-linked CYBB gene, also known as NAD (P) H oxidase 2. Approximately 260 patients with CGD have been reported in Japan, of whom 92 were shown to have mutations of the CYBB gene and 16 to have chromosomal deletions. However, there has been very little detailed analysis of the range of the deletion or close understanding of the disease based on this. We therefore analyzed genomic rearrangements in X-linked CGD using array comparative genomic hybridization analysis, revealing the extent and the types of the deletion genes. The subjects were five Japanese X-linked CGD patients estimated to have large base deletions of 1 kb or more in the CYBB gene (four male patients, one female patient) and the mothers of four of those patients. The five Japanese patients were found to range from a patient exhibiting deletions only of the CYBB gene to a female patient exhibiting an extensive DNA deletion and the DMD and CGD phenotype manifested. Of the other three patients, two exhibited CYBB, XK, and DYNLT3 gene deletions. The remaining patient exhibited both a deletion encompassing DNA subsequent to the CYBB region following intron 2 and the DYNLT3 gene and a complex copy number variation involving the insertion of an inverted duplication of a region from the centromere side of DYNLT3 into the deleted region.